Method for preparing carbon dioxide adsorption material by using waste FCC (Fluid Catalytic Cracking) catalyst
By grinding and crystallizing the waste FCC catalyst, an adsorption material with highly selective adsorbed carbon dioxide is prepared, which solves the environmental pollution and high cost problems of waste catalyst treatment and regeneration technology, and achieves efficient secondary utilization of waste catalysts and energy conservation and emission reduction.
Patent Information
- Application Number
- CN202411482940.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-14
AI Technical Summary
After the waste FCC catalyst is inactivated during use, improper handling will lead to environmental pollution, and existing regeneration technologies require high concentrations of acid liquid consumption and high cost.
The waste FCC catalyst is recycled and utilized through grinding and crystallization reactions to prepare adsorbent materials that are highly selectively adsorbed carbon dioxide, avoiding pickling and high-temperature activation steps, and reducing energy consumption and pollution.
The efficient secondary utilization of waste FCC catalyst is achieved, and materials that are highly selectively adsorbed carbon dioxide are prepared, saving energy consumption and water resources, and reducing environmental pollution.
Smart Images

Figure CN119608104A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical industry, and in particular to a method for preparing a carbon dioxide adsorption material by utilizing a waste FCC catalyst. Background Art
[0002] Catalytic cracking (FCC) catalyst is the most widely used catalyst in the current oil refining industry. It has the characteristics of good catalytic activity, good selectivity, stability and strong anti-poisoning ability. At present, the annual consumption of FCC catalyst is huge, but a large amount of waste FCC catalyst is also generated due to deactivation during use. The main reasons for the deactivation of waste FCC catalyst include coking, carbon deposition and mechanical wear and impact. The metal ions nickel (Ni), iron (Fe) and vanadium (V) contained in the raw oil are deposited on the surface of the FCC catalyst, causing the catalyst to be poisoned and deactivated. Burying is currently the main way to treat waste FCC catalysts, but after burial, the harmful heavy metals in the waste FCC catalysts will leach out through rainwater erosion and pollute groundwater, soil and rivers, causing environmental pollution. Severely poisoned waste FCC catalysts are generally difficult to regenerate. If they are not properly treated, they will pose a serious threat to the human living environment. Therefore, the effective treatment and utilization of waste FCC catalysts has become a very important and urgent issue.
[0003] Although the spent FCC catalyst has lost its catalytic activity, most of its internal molecular sieve structure is retained. Therefore, in recent years, de-poisoning metal resurrection catalyst has become one of the main research directions for the comprehensive utilization of waste refining catalysts. In response to the problem of de-metallization and resurrection of catalysts, the most commonly used method is to use inorganic or organic acids to leach Ni, Fe, and V from the spent FCC catalyst. However, this process requires a large amount of high-concentration acid solution, and although a relatively high leaching rate can be obtained, the aluminum in the molecular sieve will dissolve and the skeleton will collapse, resulting in it being unable to be reused.
[0004] The synthesis of zeolite molecular sieves using waste FCC catalysts provides a new way for the resource utilization of waste FCC catalysts, which has good economic benefits and application prospects. At present, the types of zeolite molecular sieves synthesized using waste FCC catalysts are relatively single, and the waste FCC catalysts need to be pretreated before the preparation of the molecular sieves. On the one hand, acid washing is required to remove the poisoning metals in the waste FCC catalysts; on the other hand, in addition to Y zeolite molecular sieves, there are some inert components in the FCC catalysts, which are not easy to be directly used for the synthesis of zeolites. Chemical phase changes are required to destroy the structure. The most common method is high-temperature solid-phase alkali melting method. However, this activation method often needs to be carried out at high temperatures, which further increases the cost of resource utilization of waste FCC catalysts. Therefore, it is very important to develop a low-energy and low-pollution secondary resource utilization technology for waste FCC catalysts.
[0005] On the other hand, the climate change caused by greenhouse gas (mainly CO2) emissions not only has a significant impact on the environment, but also has an impact on the economic and social levels that cannot be underestimated. Therefore, it is necessary to minimize greenhouse gas emissions. At present, in addition to improving the efficiency of fossil energy, carbon capture and storage are considered to be effective methods to mitigate climate change. Among them, solid adsorption material CO2 capture technology has become the focus of current research due to its environmental friendliness, high efficiency, simple equipment, and easy operation. Therefore, if CO2 adsorption materials can be prepared using waste FCC catalysts, the secondary utilization of resources can be fully realized. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a carbon dioxide adsorbent material using waste FCC catalysts. The present invention recycles the waste FCC catalysts only by grinding and crystallization reaction to prepare an adsorbent material that can adsorb carbon dioxide with high selectivity. The recycling method has a simple process and lower solvent energy consumption, and achieves energy conservation and emission reduction while fully reusing resources.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a carbon dioxide adsorbent material using a waste FCC catalyst, comprising the following steps: S1: Mix and grind the waste FCC catalyst containing iron, silicon source, sodium hydroxide and molecular sieve seed crystals.
[0008] S2: The obtained mixture is mixed with water and then subjected to a crystallization reaction to obtain a carbon dioxide adsorbent having a high selectivity for carbon dioxide.
[0009] The present invention recycles the waste FCC catalyst only through simple grinding and crystallization reaction, and obtains an adsorbent material that can adsorb carbon dioxide with high selectivity. The recycling method does not need to acid-wash the waste FCC catalyst to remove metal elements such as Ni, Fe, and V, and does not need an additional high-temperature activation step. Therefore, the process is simple, the solvent energy consumption is lower, and energy conservation and emission reduction are achieved while fully reusing resources.
[0010] The reason why the present invention does not need to use acid washing to remove metal elements such as Ni, Fe, and V in the waste FCC catalyst is that in the prior art, waste FCC catalysts are recycled to prepare new catalysts, and the above metal elements will affect the catalytic activity. However, what is ultimately produced by the present invention is a carbon dioxide adsorption material rather than a catalyst, so the presence of the above metal elements will not only not affect its physical adsorption performance, but will be more conducive to the selective adsorption of carbon dioxide. For example, the presence of an appropriate amount of iron in the waste FCC catalyst will cause the iron element to preferentially occupy the T site of the molecular sieve framework; as the iron content increases, the 12-MR microchannels in the molecular sieve contain more iron species, and partial blockage of the iron species in the microchannel will cause the intermittent narrowing of the 12-MR micropores of the molecular sieve, allowing CO2 to pass smoothly, but N2 cannot pass, thereby improving the selectivity of CO2 / N2.
[0011] The reason why the present invention does not require a high-temperature alkali melting step to remove the inert components in the waste FCC catalyst is that the FCC catalyst is mainly composed of three parts, namely molecular sieves (Y molecular sieves and ZSM-5 molecular sieves), kaolin and a binder. The main components of the molecular sieve are SiO2 and Al2O3, and the main component of kaolin is kaolinite, whose crystal chemical formula is 2SiO2·Al2O3·2H2O, and its theoretical chemical composition is 46.54% SiO2, 39.5% Al2O3, and 13.96% H2O; commonly used binders include aluminum sol and silica sol (common raw materials in the molecular sieve synthesis process). In the synthesis of zeolite molecular sieves, a molecular sieve rotation method can be used to prepare another zeolite molecular sieve. In summary, when using waste FCC catalysts as raw materials to prepare the carbon dioxide adsorbent of the present invention, it is not necessary to use high-temperature alkali melting to remove inert components.
[0012] Preferably, in S1, the molar ratio of Na2O, SiO2, Al2O3, H2O and seed crystal in the raw materials is controlled to be (0.075~0.225) : 1 : (0.033~0.167) : (2~8) : (0.01~0.1) during batching.
[0013] The present invention finds that the molar ratio of Na2O, SiO2, Al2O3, H2O and seed in the raw material has a significant effect on the adsorption selectivity of the finally formed adsorbent material to carbon dioxide. Specifically: The present invention finds that when Na2O / SiO2 is too low, the main component of the product is amorphous SiO2, which hardly adsorbs CO2; when Na2O / SiO2 is too high, the main component of the product is dense phase, and the pores of the dense phase are very small, which hardly adsorbs CO2. When SiO2 / Al2O3 is too low, the main component of the product is amorphous SiO2, which hardly adsorbs CO2; when SiO2 / Al2O3 is too high, a lot of external silicon sources are required, and the goal of "turning waste into treasure" cannot be achieved. When H2O / SiO2 is too low, the main component of the product is amorphous SiO2, which hardly adsorbs CO2; when H2O / SiO2 is too high, this method requires a large amount of water resources, which is contrary to the theory of preparing zeolite molecular sieves by solvent-free method. When Seed / SiO2 is too low, the resulting MOR zeolite molecular sieve has a low crystallinity, which will reduce the CO2 adsorption capacity to a certain extent.
[0014] Preferably, the content of iron in the carbon dioxide adsorbent material is 0.3-1 wt%.
[0015] The present invention further found that: at a lower iron content, the iron element will preferentially occupy the T site of the molecular sieve framework, which is beneficial to the adsorption of CO2 to a certain extent; as the iron content increases, the 12-MR microchannel in the molecular sieve contains more iron species, and the partial blockage of the iron species in the microchannel will cause the intermittent narrowing of the 12-MR micropores of the molecular sieve, which can allow CO2 to pass smoothly, but N2 cannot pass, thereby improving the selectivity of CO2 / N2. When the iron content is too high, the excess iron species will block the pores, which is not conducive to the adsorption of CO2.
[0016] Preferably, in S1, the total amount of SiO2 and Al2O3 in the spent FCC catalyst accounts for more than 80wt%.
[0017] Preferably, in S1, the silicon source is solid silica gel.
[0018] Adding molecular sieve seeds during grinding and mixing can increase the crystallization rate and inhibit the growth of impurities.
[0019] Preferably, in S2, the temperature of the crystallization reaction is 100-200°C, and the time is 0.5-5 days.
[0020] Preferably, in S2, after the crystallization reaction, the obtained product is filtered and dried.
[0021] In a second aspect, the present invention provides a carbon dioxide adsorbent material prepared by the above method.
[0022] In a third aspect, the present invention provides the use of the carbon dioxide adsorbent material prepared by the above method in the selective adsorption of carbon dioxide.
[0023] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention recycles waste FCC catalysts to produce an adsorption material with high adsorption selectivity for carbon dioxide.
[0024] (2) The present invention recycles the waste FCC catalyst only through simple grinding and crystallization reaction. The recycling method does not need to acid wash the waste FCC catalyst to remove the metal elements therein, and does not need an additional high-temperature activation step. Compared with the traditional hydrothermal synthesis, it saves a lot of water resources. Therefore, the process steps of the method of the present invention are simple, the solvent energy consumption is lower, and energy conservation and emission reduction are achieved while fully reusing resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The XRD spectra of the spent FCC catalysts in various embodiments of the present invention are shown in FIG.
[0026] Figure 2 The following are scanning electron microscope images of the spent FCC catalysts in various embodiments of the present invention.
[0027] Figure 3 This is the XRD spectrum of the adsorption material prepared in Example 1 of the present invention.
[0028] Figure 4 This is a scanning electron microscope image of the adsorption material prepared in Example 1 of the present invention.
[0029] Figure 5 This is the XRD spectrum of the adsorption material prepared using conventional silicon aluminum sources in Comparative Example 1 of the present invention.
[0030] Figure 6 This is a scanning electron microscope image of the adsorption material prepared using conventional silicon aluminum sources in Comparative Example 1 of the present invention.
[0031] Figure 7 It is the CO2 adsorption curve diagram of different adsorption materials in the present invention.
[0032] Figure 8 This is a test graph of the CO2 / N2 (15 / 85, V / V) multi-component penetration curve of different adsorbent materials in the present invention. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Overall embodiment A method for preparing a carbon dioxide adsorbent material using a waste FCC catalyst comprises the following steps: S1: Mix and grind the waste FCC catalyst containing iron, silicon source, sodium hydroxide and molecular sieve seed crystals. When mixing the ingredients, the molar ratio of Na2O, SiO2, Al2O3, H2O and seed crystals in the raw materials is controlled to be (0.075-0.225):1:(0.033-0.167):(2-8):(0.01-0.1).
[0035] In some preferred implementation cases, the total amount of SiO2 and Al2O3 in the spent FCC catalyst accounts for more than 80 wt%.
[0036] In some preferred implementation cases, the oxide composition of each component in the spent FCC catalyst is as follows: Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[La2O3]]> <![CDATA[V2O5]]> <![CDATA[Fe2O3]]> <![CDATA[CeO2]]> other Content wt / % 39.5-49.5 36.4-46.4 3.31-5.31 0.61-2.61 0.51-2.51 0.23-2.23 margin In some more preferred implementation cases, the silicon source is solid silica gel; and the molecular sieve seed is MOR zeolite molecular sieve.
[0037] S2: The obtained mixture is mixed with water and then subjected to a crystallization reaction to obtain a carbon dioxide adsorbent having a high selectivity for carbon dioxide.
[0038] In some more preferred implementation cases, the temperature of the crystallization reaction is 100-200° C., and the time is 0.5-5 days.
[0039] In some more preferred implementation cases, after the crystallization reaction, the obtained product is filtered and dried.
[0040] In some more preferred implementation cases, the content of iron in the carbon dioxide adsorbent material is 0.3-1 wt%.
[0041] Specific Examples and Comparative Examples The waste FCC catalyst samples used in the following cases of the present invention are from a petrochemical plant in Zhejiang. The chemical composition of the waste FCC catalyst determined by XRF is shown in the following table, wherein the total content of SiO2 and Al2O3 is greater than 80%. Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[La2O3]]> <![CDATA[V2O5]]> <![CDATA[Fe2O3]]> <![CDATA[CeO2]]> other Content wt / % 44.5 41.4 4.31 1.61 1.81 1.23 5.14
[0042] The X-ray diffraction pattern of spent FCC catalyst is as follows: Figure 1 As shown in the figure, it can be seen that the spent FCC catalyst still has the structure of Y zeolite molecular sieve, which also contains kaolin; the scanning electron microscope image is shown in Figure 2 As shown, from Figure 2 It can be seen that the spent FCC catalyst still has a uniform morphology.
[0043] (I) Effect of different seed contents on products Example 1: Solid-phase synthesis of carbon dioxide adsorbent material at a seed content of 10% First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.1 seed crystal.
[0044] The results of X-ray diffraction analysis are as follows Figure 3 As shown, Figure 4 This is a scanning electron microscope (SEM) photograph of the product.
[0045] Example 2: Solid-phase synthesis of carbon dioxide adsorbent material at a seed content of 5% First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.05g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.05 seed crystals.
[0046] Example 3: Solid-phase synthesis of carbon dioxide adsorbent material at a seed content of 1% First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.01g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.01 seed crystal.
[0047] (II) Effect of different crystallization temperatures on the product Example 4: Solid-phase synthesis of carbon dioxide adsorbent material at 100°C First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.30g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallization was completed at 100°C for 5 days, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.225Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.1 seed crystal.
[0048] Example 5: Solid-phase synthesis of carbon dioxide adsorbent material at 140°C First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.17g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 140°C for 2 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.128Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.10 seed crystals.
[0049] Example 6: Solid-phase synthesis of carbon dioxide adsorbent material at 180°C First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.12g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 180°C for 1d, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.09Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.10 seed crystals.
[0050] Example 7: Solid-phase synthesis of carbon dioxide adsorbent material at 200°C First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.10g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 200°C for 0.5d, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.075Na2O / 1.0SiO2 / 0.167Al2O3 / 4H2O / 0.10 seed crystals.
[0051] (III) Effect of different H2O / SiO2 ratios on products Comparative Example 1: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of H2O / SiO2=1 First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 0.3g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 1H2O / 0.10 seed crystals.
[0052] Example 8: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of H2O / SiO2=2 First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 0.6g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 2H2O / 0.10 seed crystals.
[0053] Example 9: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of H2O / SiO2=5 First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.5g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 5H2O / 0.10 seed crystals.
[0054] Example 10: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of H2O / SiO2=6 First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.8g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 6H2O / 0.10 seed crystals.
[0055] Example 11: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of H2O / SiO2=8 First, 0.6844g of waste FCC catalyst, 0.6955g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 2.4g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.167Al2O3 / 8H2O / 0.10 seed crystals.
[0056] (IV) Effect of different SiO2 / Al2O3 ratios on products Comparative Example 2: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=4 First, 11.0266g of waste FCC catalyst, 00.5432g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 00.25Al2O3 / 4H2O / 0.10 seed crystals.
[0057] Example 12: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=8 First, 0.5133g of waste FCC catalyst, 0.7716g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.125Al2O3 / 4H2O / 0.10 seed crystals.
[0058] Example 13: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=10 First, 0.4106g of waste FCC catalyst, 0.8173g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.1Al2O3 / 4H2O / 0.10 seed crystals.
[0059] Example 14: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=15 First, 0.2738g of waste FCC catalyst, 0.8782g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.067Al2O3 / 4H2O / 0.10 seed crystals.
[0060] Example 15: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=25 First, 0.1643g of waste FCC catalyst, 0.9269g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.04Al2O3 / 4H2O / 0.10 seed crystals.
[0061] Example 16: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=30 First, 0.1369 g of waste FCC catalyst, 0.9391 g of solid silica gel, 0.25 g of sodium hydroxide and 0.10 g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2 g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.033Al2O3 / 4H2O / 0.10 seed crystals.
[0062] Comparative Example 3: Solid-phase synthesis of carbon dioxide adsorbent material under the condition of SiO2 / Al2O3=35 First, 0.1173g of waste FCC catalyst, 0.9478g of solid silica gel, 0.25g of sodium hydroxide and 0.10g of MOR molecular sieve seed crystals were weighed and placed in an agate mortar, and the above substances were ground and mixed uniformly at room temperature, and then the mixture was transferred to a reactor, and then 1.2g of water was added dropwise to the reactor, and crystallized at 120°C for 3 days, that is, completely crystallized, and the product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.188Na2O / 1.0SiO2 / 0.0286Al2O3 / 4H2O / 0.10 seed crystals.
[0063] Comparative Example 4: Hydrothermal synthesis of carbon dioxide adsorption material using conventional silicon-aluminum sources First, 0.491g NaAlO2 and 0.10g sodium hydroxide were dissolved in 4.5g water, stirred for 10min, and then 2.5g silica sol (40%) was added. After stirring for two hours, 0.10g MOR molecular sieve seed was added, and then the reaction raw materials were added to the reactor, and crystallized at 160°C for 3d to completely crystallize. The product was filtered and dried to obtain the product. According to the addition amount of each reaction raw material in this case, the molar ratio of each component is: 0.075Na2O / 1.0SiO2 / 0.125Al2O3 / 20H2O / 0.10 seed.
[0064] Its structure is analyzed by X-ray diffraction. Figure 5 As shown, Figure 6 This is a scanning electron microscope (SEM) photograph of the product.
[0065] CO2 adsorption performance test The adsorption materials in each embodiment and each comparative example were subjected to CO2 adsorption isotherm test and CO2 / N2 (15 / 85, V / V) multi-component breakthrough curve test at 298K. The results are shown in the following table. Figure 7 and Figure 8As shown, compared with the adsorption material prepared using waste FCC catalyst and the adsorption material synthesized using traditional raw materials, FCC-MOR has a larger CO2 adsorption capacity, longer CO2 retention time and greater selectivity. Therefore, the MOR zeolite molecular sieve prepared using waste FCC catalyst can be used as a selective adsorption material for CO2. However, in Comparative Example 1, due to the low water-silicon ratio, the composition of the obtained product is a combination of amorphous and MOR zeolite molecular sieves, and the presence of the amorphous makes the CO2 adsorption performance decrease; in Comparative Example 2, due to the low silicon-aluminum ratio, the composition of the obtained product is a combination of amorphous and MOR zeolite molecular sieves, and the presence of the amorphous makes the CO2 adsorption performance decrease; in Comparative Example 3, due to the high silicon-aluminum ratio, although the obtained product is MOR zeolite molecular sieve, the iron content in the product is low, which shortens the retention time of CO2 in multi-component competitive adsorption, and thus reduces the selectivity of CO2; in Comparative Example 4, the obtained product is MOR zeolite molecular sieve, which does not contain iron, so its CO2 retention time is shorter than that of the MOR zeolite molecular sieve prepared from waste FCC catalyst, and its CO2 selectivity is lower.
[0066] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0067] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon dioxide adsorbent material using waste FCC catalyst, characterized in that include: S1: mixing and grinding the waste FCC catalyst containing iron, silicon source, sodium hydroxide and molecular sieve seed crystals; S2: The obtained mixture is mixed with water and then subjected to a crystallization reaction to obtain a carbon dioxide adsorbent having a high selectivity for carbon dioxide.
2. The method according to claim 1, characterized in that: In S1, the molar ratio of Na2O, SiO2, Al2O3, H2O and seed crystal in the raw materials is controlled to be (0.075~0.225):1:(0.033~0.167):(2~8):(0.01~0.1) during batching.
3. The method according to claim 1, characterized in that: The content of iron in the carbon dioxide adsorbent material is 0.3-1 wt %.
4. The method according to claim 1, characterized in that: In S1, the total amount of SiO2 and Al2O3 in the spent FCC catalyst accounts for more than 80wt%.
5. The method according to claim 1, characterized in that: In S1, the silicon source is solid silica gel.
6. The method according to claim 1, characterized in that: In S2, the temperature of the crystallization reaction is 100-200°C, and the time is 0.5-5 days.
7. The method according to claim 1 or 6, characterized in that: In S2, after the crystallization reaction, the obtained product is filtered and dried.
8. A carbon dioxide adsorbent material, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
9. Use of the carbon dioxide adsorbent material obtained by the method according to any one of claims 1 to 7 in selective adsorption of carbon dioxide.